Ações de melhoria contínua para incrementar a qualidade e produtividade na cadeia do leite - Noal, Rosane Maria Coradini (2006)
Milk and dairy products are groceries of high nutritive value, and therefore, of easy contamination. A great part of the toxic infections that occur, according to the World Health Organization, is caused by the consume of contaminated food, and the main factors that determine these contaminations are related with the poor raw-material obtaining conditions, storage, transportation, processing, manipulation, conservation and commercialization. The present moment requires news models of management, in the milk farms and in the dairy industry. This study had as its objective to point out actions for continuous improvement, to increase the quality and productivity in the milk chain, from diagnosis made in a milk farm and in a Dairy Factory in Santa Maria/RS. The methodology used was the explanatory-descriptive-exploratory type. For the concretization of this project, in the rural property, visual observation and environmental pictures were used, which included the physical-functional structure, operational, human resources and of the flux of milk obtaining in the milking rooms, and milk. In the factory, was from analysis of the physical-functional, operational and human resources structure, which was made through the observation of the plant, visual observation of the environment e pictures of the production fluxes, as well as through data collecting in files in the management sector and verifying list of the GMP. The detailed analysis of the processes identified opportunities for improvement, and evaluation of non conformities in the rural property and factory, based in the current legislations. The evaluation instrument, applied to the locals of study, demonstrated itself to be a effective tool in the identification of factors of non conformities, made possible the elaboration of the Plan of Action 5S s, to the rural property, Manual of GMP to the Factory, and adaptation suggestions to eliminate identified flaws.